La originalidad de la economía marginalista de Jeremy Bentham - Aznar, Estrella Trincado (REVISTA PROCESOS DE MERCADO, 2005)
In this paper, we present some Bentham’s theory features that make him precursor of marginalist economics. The author described the ideas of decreasing marginal utility and equimarginality, he made a commodity classification that distinguished between an upper and a lower class of goods depending on the proximity to use and his defi-nition of property as an expectation of possession lead him to develop an economic theory based on individual information search. At the same time, he attached special importance to the figure of the innovative entrepreneur and described the market as a discovery process in which the central agent is the entrepreneur. Key words: Bentham, marginalist economics, entrepreneur. Clasificación JEL: B12. Resumen: En este artículo, se demuestra que la teoría de Jeremy Bentham es precursora de la economía marginalista. El autor intro-dujo las ideas de utilidad marginal decreciente, la equimarginalidad en el intercambio, realizó una clasificación entre bienes superiores e inferiores y su definición de la propiedad como una expectativa de pose-sión le llevó a desarrollar una teoría económica basada en la búsqueda individual de información. Así mismo, dio especial importancia a la figura del empresario innovador y describió el mercado como un pro-ceso de descubrimiento en que el agente central es el empresario. Palabras clave: Bentham, economía marginalista, empresario.